Processos sustentáveis de hidroformilação: solventes verdes, tecnologias one-pot e catalisadores de cobalto - Fábio Godoy Delolo (2022)
Considering the current scenario, the need to review anthropological activities related to the production technologies in our society is evident. The hydroformylation reaction is the most important process to obtain aldehydes. Their products and their derivatives are present in daily life society and will be present for a long time. Seeking the development of sustainable processes, various solvents were evaluated in the hydroformylation reaction. The solvent represents most of the mass involved in a chemical process and, therefore, plays a fundamental role in the overall process sustainability. Among the solvents evaluated, anisole showed the best performance and was, therefore, applied in the hydroformylation of several types of olefins, including terpenes. The results have demonstrated that anisole is an interesting solvent for hydroformylation, allowing to match catalytic efficiency with sustainability. Next, we develop a one-pot process for the functionalization of olefins performing the modification of the substrate molecule in different reaction sites simultaneously in the same reactor. The novel process developed in the present work is based on the hydroformylation and O-acylation reactions and allows the synthesis of the molecules with interesting organoleptic properties and/or intermediates for the fine chemical industry. The process was evaluated on a range of substrates, which contain in the same structure the combinations of the OH group (phenol, primary, secondary and tertiary alcohol) and C-C double bond (mono, 1,1-disubstituted, 1,2-disubstituted, trisubstituted), both aliphatic and endocyclic. It was established that in all cases anisole can be used as a solvent to improve the process sustainability. The methodology developed allows for the sustainable valorization of biorenewable raw materials in order to reduce and/or eliminate the allergenic activity of certain raw materials, boosting the respective industrial sector. Next, the hydroformylation reactions catalyzed by cobalt complexes were studied. It has been shown, that the use of phosphine oxides as promoters (in particular, triphenylphosphine oxide, a simple and low-cost substance) allows performing hydroformylation under mild conditions in the presence of a cobalt catalyst.